Healthy Living: Use Your Medicines Safely! - Paulina Wittkowsky; Linda B. Bobroff; Emily Minton (EDIS)
Medicines can help us feel better and improve our health, but if we do not use them correctly, they can make us feel worse or even cause major health problems. To use your medicines safely, keep the following tips in mind. This revised 4-page large print fact sheet was written by Paulina Wittkowsky, Linda B. Bobroff, and Emily Minton, and published by the UF Department of Family, Youth and Community Sciences, November 2014. (Photo: Thinkstock.com)